The CroMyop study: myopia progression in Croatian children and adolescents—a 15-year retrospective analysis - Varošanec, Ana Maria; Marković, Leon; Sonicki, Zdenko (Frontiers in Medicine, 2024)
Myopia is a major global health issue, especially among children and adolescents. Understanding its traits and progression is vital for proper management and prevention. This study aimed to fill a gap in research by analyzing demographic and refractive data concerning myopia among children and adolescents in Croatia, with the goal of providing insights into myopia prevalence, progression rates, and associated risk factors within the Croatian population. This retrospective study utilized a comprehensive dataset from pediatric ophthalmology clinics at the University Eye Department, University Hospital "Sveti Duh," Zagreb, Croatia. The dataset included electronic medical records spanning from January 2008 to July 2023, encompassing demographic and refractive data. Data analysis focused on individuals aged 4 to 18 years who were diagnosed with primary myopia and/or compound myopic astigmatism. Ophthalmic examinations, including visual acuity tests, cycloplegic refraction, and assessments for eye comorbidities, were conducted by experienced pediatric ophthalmologists. Statistical analysis, including t-tests, survival analysis, and logistic regression, were performed to assess myopia prevalence, progression rates, and associated factors. These analysis were adjusted for covariates such as age, parental myopia, and gender. The study included 895 individuals, 51 premyopes, 813 low myopes, and 31 high myopes. Average age of diagnosis was 11.37±3.59 y for premyopes, 11.18±3.53 y for low myopes, and 11.44±4.35 y for high myopes. Fastest progression occurred in 2021 and 2022, -0.5±0.12 D/y for premyopes and -0.45±0.1 D/y for low myopes. Premyopic progression to low myopia was associated with age 7-9 y (HR 2.42, 1.53 to 3.21) and both parents myopic (HR 920.27. 850.16 to 950.53). Low myopic individuals with both myopic parents displayed fastest 11-24 months after first visit progression rates, -0.69 (-0.52 to -0.87) D/y, while the 7-9 age group demonstrated -0.36 (-0.24 to -0.45) D/y. Low myopes aged 7-9 with baseline SE between -6 D and -4 D were more strongly associated with ≤-0.5 D progression (OR=2.0, 95% CI -1.00 to 2.39). This study highlights the importance of environmental factors, genetics, and age in addressing myopia progression among Croatian youth, urging further research for effective local intervention strategies.